UPAYA MENGEMBANGKAN POTENSI GURU DALAM MENGAJAR DI SDN LENGKONG 01 MUMBULSARI JEMBER DENGAN PENERAPAN SUPERVISI AKADEMIK MELALUI KEGIATAN WORKSHOP PADA SEMESTER GENAP TAHUN 2021/2022 - Nuraini, Fatmah (Kadikma, 2023)
The purpose of this research is to find out about the extent of mastery of teacher competence with the application of academic supervision through workshop activities. The research location is at SDN Lengkong 01, Mumbulsari District, Jember District, even semester of the 2021/2022 academic year. This research method uses school action research by performing two actions in three cycles. Each cycle consists of four stages, namely action planning, action implementation, observation of action results, and reflection. Data collection using documentation, observation, and interviews. Data collection tools with teacher personal record documents, observation sheets, and interview sheets. Data analysis uses comparative descriptive followed reflection. The results showed that through academic supervision can optimize the quality of teacher competence as shown by an average increase from cycle I 2.07 (category less / not good), and after academic supervision in groups in cycle II the average to 3.36 with the category quite good, and after academic supervision individually in cycle III the average to 4.28 with the category of very good (almost perfect).